Predictors of Outcomes of Foot Ulcers among Individuals with Type 2 Diabetes Mellitus in an Outpatient Foot Clinic - Felipe, Roy Raoul; Plata-Que, Ma. Teresa (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Objectives. To determine the risk factors for recurrence and persistence of non-healing foot ulcer resulting in minor and major amputations,. Methodology. This was an ambispective cohort analysis of persons with diabetic foot ulcers consulting at the diabetic foot clinic of East Avenue Medical Center. Data were analyzed through multiple logistic regression. Result. Two hundred sixteen patients with Type 2 Diabetes Mellitus and diabetic foot ulcers were included in the analysis; 50.9% were males and the mean age of the cohort was 55.8 ± 9.9 years. Outcomes of foot ulcers were: healed 44.5% (healed with no recurrence 30%, healed but with recurrence 14.5%) and not healed 55.5% (major amputation 11%, minor amputation, 21.5%, and persistently non-healing 23%). Multivariate logistic regression showed the following were independent risk factors for persistent non-healing ulcer: osteomyelitis (OR 66.5; CI 19.7, 217.8), smoking (OR 28.9; CI 6.8, 129.3, and peripheral arterial disease (PAD) (OR 56.8; CI 2.5, 877.2). Independent risk factors for ulcer recurrence were: plantar location of ulcer (OR 16.8; CI 6.8, 89.4), presence of more than one ulcer (OR 7.8; CI 3.6,31.6), and neuropathy (OR 11.2; CI 7.2, 19.9). For healed foot ulcers, mean healing time was 14 ± 3 weeks. Healing time was significantly reduced from 12 weeks to 4.5 weeks (p<0.001) if patients consulted earlier (within 4 weeks from sustaining an ulcer). Conclusion. Only half (55%) of patients with diabetic foot ulcers consulting in a dedicated outpatient foot clinic had an adverse outcome of foot ulcers (major amputation 11%, minor amputation, 21.5%, and persistently non-healing ulcer 23%) while a small portion (14.5%) of patients had recurrent foot ulcers. Arterial obstruction, smoking, low hemoglobin, neuropathy, and osteomyelitis increase the likelihood of healing failure while the presence of multiple ulcers, plantar location of ulcers, and neuropathy increase the risk of ulcer recurrence.